Fabrication and Characteristics Study Ni-nSiC Schottky Photodiode Detector - Ahamed, Muhanad A (Al-Nahrain Journal of Science, 2013)
In the present work, schottky photodiode have been mode on n-type SiC by depositing of thin layer of Ni. Electrical characteristics included I-V (dark and illumination) have been investigated. Ideality factor is 2.9 and barrier height is 0.52 eV was calculated from I-V and Isc-Voc characteristics, Ideality factor is 2.32 and barrier height found to be 0.54 eV, and from optoelectronic characteristics have found sensitivity results show that peak response of photodiode was 550 nm. The maximum value of Specific detectivity D*reached (1.6×1011 w-1 Hz1/2 cm).